Effects of a virtual reality serious game training program on the cognitive function of people diagnosed with schizophrenia: A randomized controlled trial - Wang, Xu; Kou, Xiaomin; Meng, Xiandong; Yu, Jianying (Frontiers in Psychiatry, 2022)
Background: Cognitive impairment persists through the course of schizophrenia and affects patients’ activities of daily living. Aim: This study aims to investigate the effects of a virtual reality (VR) serious game training program on the cognitive function of people diagnosed with schizophrenia. Methods: Sixty-four eligible people diagnosed with schizophrenia were recruited and randomly assigned to the intervention group (n=31) and the control group (n=33). The control group received standard psychiatric care. The intervention group was trained with an additional VR game twice a day for at least 10 days during hospitalization. Cognitive function was measured at enrollment and before discharge using the Brief Cognitive Assessment Tool for Schizophrenia. Results: Compared with those of the control group, the results of the working memory (t=3.463, Cohen’s d=0.87, p=0.001) and executive function (TMTA: Z=-2.272, Cohen’s d=0.59, p=0.023; TMTB:Z=-2.365, Cohen’s d=0.62, p=0.018) of the intervention group after intervention were significantly better. However, there was no significant difference in the results of social cognition (Z=-1.394, Cohen’s d=0.35, p=0.163) between the two groups. Conclusion: Intensive active virtual reality serious game training in addition to standard psychiatric care can significantly improve working memory and executive function in people diagnosed with schizophrenia. Implications for practice: When helping improve the cognitive function of people diagnosed with schizophrenia, mental health professionals should identify cognitive domains to be enhanced and develop corresponding serious game training strategies.